MASS REARING OF QUEEN BEES, APIS MELLIFERA L. (HYM: APIDAE) FOR BEE COLONY DEVELOPMENT RAISED UNDER THE TEMPERATE CONDITIONS OF KASHMIR - AHMAD , SHEIKH BILAL; AHMAD DAR, SHAHNAWAZ (The Bioscan, 2013)
This experiment was carried out to determine the differences in terms of raising queens by different rearing methods i.e. queenright and queenless colonies. The larval acceptance rates among rearing groups were found highly significant in the month of May and June (p<0.01) and significant in July (p<0.05). The graft acceptance rate in queenright colonies and queenless colonies was 83 and 79% respectively. The mean pupal weight of the queen pupae in the queenright colony was not significantly different from the mean pupal weight of the queenless colony (t = 1.13, p > 0.05). The mean length of sealed queen cell was found 26.60±0.16 mm in queenright colonies, while the same values were measured as 31.00±0.13 mm in queenless colonies (t = 8.24, p < 0.001). Mean mating rates of queen bees in queenright and queenless colonies were found to be 90.77 and 87.77% respectively. The pre-oviposition period in both queenright and queenless colonies had no significant difference among the two methods, howver, the emergence weight was 202.19±8.25 mg in queenright colonies and 197.34±7.44 mg in queenless colonies.